Preventing Indigenous youth homelessness in Canada: A qualitative study on structural challenges and upstream prevention in education. Issue 4 (24th August 2021) - Ansloos, Jeffrey Paul; Wager, Amanda Claudia; Dunn, Nicole Santos
Abstract: Drawing on a partnership with a group of Indigenous youth experiencing homelessness in Vancouver, Canada, this study identifies four structural challenges that have impacted them and four actionable upstream strategies to further prevent youth housing precarity. As a secondary analysis of a community‐engaged study with youth experiencing homelessness, we conducted a thematic analysis with qualitative data, which included qualitative interviews with five young people and researcher observations. The results reflect the racial, colonial, and economic concerns that impact Indigenous youth experiencing homelessness. The four actionable upstream solutions highlight human rights‐based approaches to homelessness, ranging from advancing and strengthening public services, transitional justice processes, and cultural and socioeconomic safety. This study provides strategies to promote Indigenous youth wellbeing and decrease risk of housing precarity, while centering and drawing from youth knowledge production. Strengths and limitations of the study are also discussed.